2022
DOI: 10.1159/000525090
|View full text |Cite
|
Sign up to set email alerts
|

Activated Platelets, the Booster of Chronic Kidney Disease and Cardiovascular Complications

Abstract: <b><i>Background:</i></b> Chronic kidney disease (CKD) has become a global public health problem nowadays. As cardiovascular diseases (CVDs) are the primary cause of death in advanced CKD patients, much attention has been paid to resolving their cardiovascular complications. However, managing CKD and cardiovascular complications is still a big challenge for nephrologists, as satisfactory treatments are still lacking. Platelets, the second most abundant cells in the blood, are the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that PMPs transfer their genetic contents, such as miRNAs, to target cells and affect gene expression in vitro [15][16][17][18][19][20][21][22]. In our study, we found that the molecular ndings were consistent with the results of reduced cell proliferation in cell culture.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that PMPs transfer their genetic contents, such as miRNAs, to target cells and affect gene expression in vitro [15][16][17][18][19][20][21][22]. In our study, we found that the molecular ndings were consistent with the results of reduced cell proliferation in cell culture.…”
Section: Discussionsupporting
confidence: 88%
“…Uremic toxin accumulation leads to increased oxidative stress, 11 inflammation, 12 , 13 and increased platelet dysfunction, 14 , 15 , 16 whereas phosphate retention contributes to vascular calcification 17 and parathyroid mediated bone problems ( Figure 1 ). 18 , 19 In this section, we will limit our discussion to novel mechanisms pertaining to inflammation and platelet-related pathophysiology in CKD because other mechanisms were extensively reviewed by others, 10 , 20 , 21 , 22 , 23 , 24 and managing immune cells and inflammation is an active area of research that would potentially generate new therapies for CKD management.
Figure 1 Mechanisms for excessive CV events in patients with CKD arising from reduced excretion from the kidney or reduced hormone (erythropoietin and calcitriol) production from the kidney.
…”
Section: Burdenmentioning
confidence: 99%
“…Thus, blocking the generation and release of EVs was found to reduce blood pressure in hypertensive rats [ 203 ]. Furthermore, an increase in circulatory EC-EV levels has been found in patients with endothelial dysfunction [ 204 ], obstructive sleep apnea [ 205 ], obesity [ 206 , 207 ], renal failure [ 208 ], coronary artery disease [ 209 ], myocardial infarction [ 210 , 211 , 212 ], β-thalassemia [ 213 ], and stroke [ 214 ]. Nevertheless, it is not clear if the increase in their number contributes to these conditions.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%